Functional at Scale. - ERIKSEN, MARIUS (Communications of the ACM, 2016)
The article discusses three computer science abstractions that follow a particular style of functional programming including futures, services, and filters. According to the article, programmers can construct complex software while simultaneously preserving the ability to reason regarding the accuracy of constituent aspects.